Killing the mob : the fight against organized crime in America - O'Reilly, Bill; Dugard, Martin (O'Reilly, Bill. Killing series., 2021)
Covering the period from the 1930s to the 1980s, O'Reilly and Dugard start by tracing the prohibition-busting bank robbers of the Depression Era. Following the rise of organized crime, they highlight the creation of the Mafia Commission, the power struggles within the "Five Families," and the growth of the FBI under J. Edgar Hoover. In addition to the mob battles to control Cuba, Las Vegas and Hollywood, O'Reilly and Dugard follow the personal war between the U.S. Attorney General Bobby Kennedy and legendary Teamsters boss Jimmy Hoffa. Their book shows just how deeply the Mob has influenced every aspect of American life. -- adapted from jacket